Optimisation of the backward giant circle on asymmetric bars - Hiley, M. J.; Yeadon, M. R. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
The purpose of this study was to optimise the release window in the backward giant circle performed prior to release for a double layout somersault dismount from the asymmetric bars. An additional aim was to investigate the effect of requiring the optimal technique to be robust to perturbations in timing of the changes in joint angles. A planar computer simulation model was used to maximise the release window (Hiley and Yeadon, 2005) of a female gymnast by manipulating the joint angle time histories during the giant circle prior to release. Optimisations were performed where the timing of the joint actions at the shoulder and hip were perturbed in order to obtain solutions that were robust to such perturbations. Joint angle time histories were limited by muscle data scaled from a male gymnast. Although introducing the requirement for robustness into the optimised giant circle technique reduced the size of the release windows more consistent performances were achieved.